2019
DOI: 10.1021/acs.macromol.9b01378
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of Stress Interaction Effects from Atomic Force Spectroscopy Data across Polymer−Particle Interfaces

Abstract: Atomic force microscopy (AFM) is a powerful technique for imaging polymer nanocomposites as well as other systems with heterogeneous material properties on the nanoscale. However, the quantitative measurement of modulus is highly susceptible to convoluting structural effects due to the finite tip radius and stress field interactions with particles and substrates which are often termed the "substrate effect" or "thin film effect". We present an empirical master curve that can model the change in measured modulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
(134 reference statements)
2
9
0
Order By: Relevance
“…To confirm that the extracted modulus from AFM is not heavily influenced by substrate effects, the force–displacement curves from the AFM indentation experiment were replicated with FEM. The relevance of continuum-scale modeling with FEM for small-scale indentations has been demonstrated in previous work. , As expected, the FEM stress intensity field shows that at 2 nm of indentation, a large portion of the stress field is transferred to the substrate layer (Figure a) . Additional details on the FEM, including visualization of the meshing is shown in Figure S8.…”
Section: Resultssupporting
confidence: 73%
“…To confirm that the extracted modulus from AFM is not heavily influenced by substrate effects, the force–displacement curves from the AFM indentation experiment were replicated with FEM. The relevance of continuum-scale modeling with FEM for small-scale indentations has been demonstrated in previous work. , As expected, the FEM stress intensity field shows that at 2 nm of indentation, a large portion of the stress field is transferred to the substrate layer (Figure a) . Additional details on the FEM, including visualization of the meshing is shown in Figure S8.…”
Section: Resultssupporting
confidence: 73%
“…Multiparametric mechanical property maps of polymer films, 144 polymer blends 145,146 and block co-polymer thin films 147 are readily obtained. The interfacial region between a rubber matrix and silica nanoparticles was studied by using both nanoscale rheology 107,148 and standard FV. 149 These samples might be used as models of the internal structure of low rolling resistance tires.…”
Section: Force-volume Applicationsmentioning
confidence: 99%
“…As there is no exact solution to this problem, a number of numerical models have been proposed to fit experimental data. Even though prior density-functional theory (DFT) simulation and chemomechanical simulation combined with transmission electron microscopy revealed the elastoplastic deformation of silicon during lithiation/delithiation, our understanding of the plastic deformation of SEIs is still limited. Wang et al studied the deformation of the interface formed with silicon and inorganic species in SEIs (LiF and Li 2 O) with first principle simulation and revealed that SEIs deform plastically by forming delocalized voids .…”
Section: Introductionmentioning
confidence: 99%